2023
DOI: 10.1111/cns.14495
|View full text |Cite
|
Sign up to set email alerts
|

Oligomer‐Aβ42 suppress glioma progression via potentiating phagocytosis of microglia

Jie Lu,
Zhenning Wang,
Zhenqiang He
et al.

Abstract: AimsGlioma is characterized by an immunosuppressed environment and a poor prognosis. The accumulation of Amyloid β (Aβ) leads to an active environment during the early stages of Alzheimer's disease (AD). Aβ is also present in glioma tissues; however, the biological and translational implications of Aβ in glioma are elusive.MethodsImmunohistochemical (IHC) staining, Kaplan–Meier (KM) survival analysis and Cox regression analysis on a cohort of 79 patients from our institution were performed to investigate the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
(113 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, it was demonstrated that BACE-1 is expressed in tumor promoting macrophages and administration of MK-8931 along with IR was able to suppress malignant GBM growth in-vivo. Interestingly, oligomers of beta amyloid protein that are associated with AD can stimulate microglia phagocytotic activity against glioma cells [119]. As with many neurodegenerative disorders, microglia dysfunction seems to be a central feature of both gliomagenesis and AD [120].…”
Section: Bace-1mentioning
confidence: 99%
“…Furthermore, it was demonstrated that BACE-1 is expressed in tumor promoting macrophages and administration of MK-8931 along with IR was able to suppress malignant GBM growth in-vivo. Interestingly, oligomers of beta amyloid protein that are associated with AD can stimulate microglia phagocytotic activity against glioma cells [119]. As with many neurodegenerative disorders, microglia dysfunction seems to be a central feature of both gliomagenesis and AD [120].…”
Section: Bace-1mentioning
confidence: 99%